Sodium/hydrogen‐exchanger‐2 modulates colonocyte lineage differentiation. (21st January 2022) - Nikolovska, Katerina; Cao, Li; Hensel, Inga; Di Stefano, Gabriella; Seidler, Anna Elisabeth; Zhou, Kunyan; Qian, Jiajie; Singh, Anurag Kumar; Riederer, Brigitte; Seidler, Ursula
Abstract: Aim: The sodium/hydrogen exchanger 2 (NHE2) is an intestinal acid extruder with crypt‐predominant localization and unresolved physiological significance. Our aim was to decipher its role in colonic epithelial cell proliferation, differentiation and electrolyte transport. Methods: Alterations induced by NHE2‐deficiency were addressed in murine nhe2 −/− and nhe2 +/+ colonic crypts and colonoids, and NHE2‐knockdown and control Caco2Bbe cells using pH‐fluorometry, gene expression analysis and immunofluorescence. Results: pHi ‐measurements along the colonic cryptal axis revealed significantly decreased intracellular pH (pHi ) in the middle segment of nhe2 −/− compared to nhe2 +/+ crypts. Increased Nhe2 mRNA expression was detected in murine colonoids in the transiently amplifying/progenitor cell stage (TA/PE). Lack of Nhe2 altered the differentiation programme of colonic epithelial cells with reduced expression of absorptive lineage markers alkaline phosphatase (iAlp), Slc26a3 and transcription factor hairy and enhancer‐of‐split 1 (Hes1), but increased expression of secretory lineage markers Mucin 2, trefoil factor 3 (Tff3), enteroendocrine marker chromogranin A and murine atonal homolog 1 (Math1). Enterocyte differentiation was found to be pHi dependent with acidic pHi reducing, and alkaline pHi stimulating the expression of enterocyte differentiation markers in Caco2Bbe cells. A thicker mucus layer, longer crypts and an expanded brush border membrane zone of sodium/hydrogen exchanger 3 (NHE3) abundance may explain the lack of inflammation and the normal fluid absorptive rate in nhe2 −/− colon. Conclusions: The results suggest that NHE2 expression is activated when colonocytes emerge from the stem cell niche. Its activity increases progenitor cell pHi and thereby supports absorptive enterocyte differentiation.